Kur’an-ı Kerim’de kurtuluş kavramı - Candan, Fatma (My University, 1999)
THE CONCEPT OF SALVATION IN THE KUR`AN ABSTRACT This thesis is composed of three chapters. In the first chapter, the concepts which explain the salvation directly and indirectly are analyzed. The main concepts are najhat(necat), falakh(felak), and favz(fevz) which mean the absolute success and salvation of the human being in the hereafter by not going against a life that Allah required human being to live, not being punished as a result of this obedience. Then the elements of salvation are discussed within the context of practice, which is a result of faith in human life, and faith. The answers of the questions like whether only the faith is sufficient for salvation or not, should faith lead to practice in life or not, can it be said as faith if the person accepts some elements of faith, is it necessary to practice in the way faith orders for salvation, are searched from Kur'an. In the second chapter the means of salvation are examined like namaz, infakh(infak), takhva (takva), jihad(cihat) under sub-titles. In the third chapter the barriers in front of the salvation are examined according to the context of faith and practice. In conclusion, to reach salvation which Kur'an defines, it is necessary to have faith which rules the life of the human being and practice that is the result of faith. Practices are not only practicing some definite rituals, but deeds which affect the general way of life that believer lives. Also the principles of Kur'an not only promise salvation in the hereafter for individuals but also on earth, for individual, for society and even for civilizations. THE CONCEPT OF SALVATION IN THE KUR`AN

This thesis is composed of three chapters. In the first chapter, the concepts which explain the salvation directly and indirectly are analyzed. The main concepts are najhat(necat), falakh(felak), and favz(fevz) which mean the salvation of the human being in the hereafter by living a life that Allah wanted human being to live, not being punished as a result of this obedience. Then the elements of salvation are analyzed within the perspective of faith and practice that is a result of faith in human life. The answers of the questions like whether the faith is sufficient enough for salvation or not, should faith lead to practice in life or not, can it be said as faith if the person accepts some elements of faith, is it necessary to practice in the way faith orders, for salvation, are searched from Kur'an. In the second chapter the things which lead to salvation are explained and analyzed like namaz, infakh(infak), takhva (takva), jihad(cihat) under each title. In the third chapter the barriers that prevents person to reach salvation are explained according to the criteria of faith and practice. In conclusion as a result of this research, to reach salvation which Kur'an defines, it is necessary to have faith which rules the life of the human being and practice that is the result of faith. Practices are not only practicing some definite rituals, but deeds which affect the general way of life that believer lives. Also the principles of Kur'an not only promise salvation in the hereafter but also on earth, in individual, social and civil life.
Keywords: ÇEŞİTLİ KONULAR; KUR’AN-I KERİM